The importance of illness severity and multimorbidity in the association between mental health and body weight in psoriasis: Cross‐sectional and longitudinal analysis. Issue 4 (19th April 2022) - Pavlova, Neli T.; Moss‐Morris, Rona; Smith, Catherine; Carr, Ewan; Rayner, Lauren; Picariello, Federica
Abstract: Background: High body weight is common in psoriasis and is associated with depression and anxiety. Past studies are mostly cross‐sectional and may underestimate the role of demographic and illness‐related factors in the association between mental health and body weight in psoriasis. Objectives: This study explored the association between depression and anxiety with waist circumference and body mass index (BMI) cross‐sectionally and at 12 months follow‐up, adjusting for demographic and illness‐related factors in people with psoriasis. Method: Routine psoriasis care data were combined with data on depression and anxiety from a large specialist psoriasis centre. The analytical samples consisted of patients with complete data on either waist circumference ( N  = 326 at time 1; N  = 191 at follow‐up) or BMI ( N  = 399 at time 1; N  = 233 at follow‐up) and corresponding mental health, demographic, and illness‐related information. Associations between weight‐related outcomes and mental health variables were assessed at time one and at 12 months follow‐up, after adjusting for demographic and illness‐related factors. Results: We found no evidence of associations between mental health and waist circumference or BMI, after adjusting for age, gender and illness‐related factors. Higher age, male gender and illness‐related factors, specifically multimorbidity and psoriasis severity, were positively associated with waist circumference and BMI at both time points. Conclusion: This study revealed the important role of factors related to illness severity in body weight in psoriasis. The contribution of depression and anxiety to weight was not observed here likely due to the sample and methodology used. Future work should explore other psychosocial factors such as weight‐related attitudes and emotional eating in the context of weight in psoriasis, to help inform the development of successful weight‐management treatments.